Ambidexterity as a dynamic capability in the globalization of the multinational business enterprise (MBE): Case studies of AB Volvo and IKEA. Issue 1 (February 2017) - Vahlne, Jan-Erik; Jonsson, Anna
Abstract: Most current research argues that globalization of companies is a myth. In spite of this Swedish firms have managed to globalize successfully according to a study byVahlne and Ivarsson (2014) . On a general level this is because they managed to build strong advantages and learned to overcome barriers constituted by cultural, institutional and geographic distance. We elaborate on the expectation that organizational ambidexterity has explanatory power for profitable globalization. We perform case studies of IKEA and AB Volvo to motivate our expectation and illustrate how these firms have been able, or not able, to balance and manage the simultaneous processes of exploration and exploitation. Ambidexterity is included in the package of dynamic capabilities affecting the globalization process positively. We find that being proactive in exploration and improving on the effectiveness in exploitation may lead to successful globalization performance.